Influence of ultrasound on the rehydration of dried sea cucumber (Stichopus japonicus). (June 2016) - Zhang, Longtao; Huang, Xuhui; Miao, Song; Zeng, Shaoxiao; Zhang, Yi; Zheng, Baodong
Abstract: Rehydration capacity, water distribution, and microstructure of sea cucumbers subjected to ultrasound-assisted rehydration (UAR) were investigated. Rehydration ratio and water holding capacity (WHC) were found to increase when ultrasound power was increased from 100 W to 300 W, to increase when ultrasound frequency was decreased from 45 KHz to 28 KHz. Nuclear magnetic resonance analysis revealed that water mobility increased with increasing ultrasound power, resulting in more immobilized water and free water, which facilitated better and faster water uptake. Analysis of scanning electron microscope micrographs revealed that with the accelerated water uptake, sea cucumber swelled faster and formed a structure with higher porosity which increased water uptake even faster and led to an accelerated rehydration and higher WHC. Combined with UAR, the rehydration efficiency of dried sea cucumber was increased 12-fold, and 44 h were saved in the rehydration procedure without any negative effect on texture. Highlights: Ultrasound treatment could accelerate the rehydration of dried sea cucumber. Contents of immobilized water and free water were all increased by ultrasound. Microstructure of sea cucumber was changed to be porous by ultrasound.